The TGF-β System As a Potential Pathogenic Player in Disease Modulation of Amyotrophic Lateral Sclerosis - Peters, Sebastian; Zitzelsperger, Eva; Kuespert, Sabrina; Iberl, Sabine; Heydn, Rosmarie; Johannesen, Siw; Petri, Susanne; Aigner, Ludwig; Thal, Dietmar R.; Hermann, Andreas; Weishaupt, Jochen H.; Bruun, Tim-Henrik; et al. (Frontiers in Neurology, 2017)
Amyotrophic Lateral Sclerosis (ALS) represents a fatal orphan disease with high unmet medical need, and a life time risk of approx. 1 / 400 persons per population. Based on increasing knowledge on pathophysiology including genetic and molecular changes, epigenetics, and immune dysfunction, inflammatory as well as fibrotic processes may contribute to the heterogeneity and dynamics of ALS. Animal and human studies indicate dysregulations of the TGF-ß system as a common feature of neurodegenerative disorders in general and ALS in particular. The TGF-ß system is involved in different essential developmental and physiological processes, and regulates immunity and fibrosis, both affecting neurogenesis and neurodegeneration. Therefore, it has emerged as a potential therapeutic target for ALS: a persistent altered TGF-ß system might promote disease progression by inducing an imbalance of neurogenesis and neurodegeneration. The current study assessed the activation state of the TGF-ß system within the periphery/in life disease stage (serum samples) and a late stage of disease (CNS tissue samples), and a potential influence upon neuronal stem cell activity, immune activation, and fibrosis. An upregulated TGF-ß system was suggested with significantly increased TGF-ß1 protein serum levels, enhanced TGF-ß2 mRNA and protein levels, and a strong trend towards an increased TGF-ß1 protein expression within the spinal cord. Stem cell activity appeared diminished, reflected by reduced mRNA expression of neuronal stem cell markers Musashi-1 and Nestin within spinal cord - paralleled by enhanced protein contents of Musashi-1. Doublecortin mRNA and protein expression was reduced, suggesting an arrested neurogenesis at late stage ALS. Chemokine/cytokine analyses suggest a shift from a neuroprotective towards a more neurotoxic immune response: anti-inflammatory chemokines/cytokines were unchanged or reduced, expression of pro-inflammatory chemokines/cytokines were enhanced in ALS sera and spinal cord post mortem tissue. Finally, we observed upregulated mRNA and protein expression for fibronectin in motor cortex of ALS patients which might suggest increased fibrotic changes. These data suggest that there is an upregulated TGF-ß system in specific tissues in ALS that might lead to a “neurotoxic” immune response, promoting disease progression and neurodegeneration. The TGF-ß system therefore may represent a promising target in treatment of ALS patients.